Potable water generation from atmospheric moisture in coastal areas using the thermoelectric effect - Sameh Tawfik Abd Elfattah (Maritime Research and Technology, 2022)
Although water covers more than two-thirds of the globe’s area by a percentage of approximately 70 %, safe potable water is still scarce and therefore many countries where freshwater resources are scarce have directed to conduct many research and studies to find a suitable way to provide potable water, from this standpoint, many countries that possess coasts on the sea, including Egypt, have tended to desalinate seawater, but this method is very expensive and may be disrupted for various technical reasons such as lack of energy to operate or damage mechanical parts, and this is what happened recently in the Egyptian northern coast and the Red Sea islands. They depend on desalination plants or bottles of mineral water extracted from wells to meet their potable water needs. This article aims to solve the problem of potable water scarcity in the northern coast of Egypt, which is characterized by the high relative humidity of air in the atmosphere (60-80%) by designing a portable potable water capture device that depends on the (Peltier Effect) and takes the energy necessary to operate it from solar energy. This device can generate 2.86 L/h of fresh potable water at a temperature of 30 OC and Relative humidity of R.H = 60 %.